Receivers location privacy in avionic crowdsourced networks: Issues and countermeasures - Savio Sciancalepore (16864152) (2021)
The lack of message encryption characterizing wireless avionic protocols, including Automatic Dependent Surveillance - Broadcast (ADS-B), recently favored the rise of a few communities that, gathering data collected by receivers at the ground or in space, offer advanced services, while at the same time releasing the cited data to the public. In this context, hiding the location of an ADS-B receiver could be useful for several reasons, including military and privacy aspects. Therefore, taking into account these considerations, the data provided by a few antennas in one of the most popular crowdsourcing platforms, Opensky Network, are released removing any information that could lead to their direct location identification. In this manuscript, we investigate the effectiveness of protecting location privacy in avionic crowdsourced networks. As a worst-case scenario, we demonstrate that, when a feasible number of receivers are deployed in the same area of a protected one, due to the nature of involved ADS-B data, standard time-based localization schemes can identify the location of any protected receiver. Our model, applied to real data, can identify the location of a protected receiver with an error ranging from 0.9 km to 2.6 km, depending on the target sensor—while the location uncertainty induced by the anonymization technique was expected to be of approximately 450 km. Our findings, supported by an extensive experimental campaign run over real data, apply to a variety of potentially protected receivers. Moreover, we also provide effective countermeasures to increase receivers’ location privacy. Finally, we discuss the trade-offs implied by the cited countermeasures, showing that it is possible to increase location privacy while not decreasing data utility. Other Information Published in: Journal of Network and Computer Applications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jnca.2020.102892